The Role of the Structural. AdJustment Programmes in the Deepening of Gender Imbalance in the less Developed Countries (LDCS) (Journal of Science and Technology, 2016)
The structural adjustment programmes (SAPs) were introduced by the World Bank with the view to correcting economic, human and trade crises which prevail throughout the economies of the third world countries. However, these programmes have not achieved the desired impact in the economies of the countries. An evealuation of the role of women and men as producers and reproducers in some sectors of the economy clearly indicate the differential impact of the policies.The adverse effects of such programmes fall disproportionately on women; and these have resulted in an increase of their workload and pressure on their time. The major elements in an adjustment strategy that may incorporate men and women into the adjustment process in an equitable way must ensure that special attention is paid to the low-income households.